Christlikeness: An Attempt to Build Christian Spirituality for Indonesian Millennial Generation - Han, Chandra; Mamahit, Henny; Panggara, Robi (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
Christlikeness is the essence of the Christian life. Efforts to build spirituality in the era of technological progress have been widely analyzed, including for the millennial generation but are more at the level of phenomena. In general, the millennial generation is understood as those who were born in the range of 1987-2001. The contemporary lie in the world today is full of massive technological influence that changes human social life and even human spiritual life, especially creating the millennial generation. A fundamental question to be answered is how to build a spirituality that is relevant for the millennial generation in Indonesia. This article aims to demonstrate that attempts to build spirituality for the millennial generation in accordance with their characteristic must be based on and simultaneously aimed at being in the Christlikeness. This article will employ the literature method from books and journal articles. Specifically, most of the journal articles will cover the research within the last 10 years. There are three stages of analysis carried out, namely:Â  first, conducting a study on the characteristics of the millennial generation specifically in Indonesia, second, demonstrating the essence of spirituality which is Christlikeness by examining Luke 9:23, and thirdly efforts to build a spirituality that is relevant to the Christian millennial generation in Indonesia. Conclusions are the final part of this article. The implication of this research both theoretically and practically is addressed to the church, the parents, and Christian educators who deal with the millennials. There is an urgency for to understand the characteristics of the millennials that they can build their spirituality. Furthermore, all who deal with the millennials must provide a relevant context for the millennials such as technology, their spirit of freedom, the attachment to the family. The essence of spirituality which is Christlikeness must be delivered through all these characteristics.